Storage of cerrado fruit-enriched sweet bread - Melo, Rafaela da Silva (2020)
The Brazilian Cerrado stands out for the biodiversity of fruit species with great potential for food use. Among these species, the marolo (Annona crassiflora Mart.) and pequi (Caryocar brasiliense Camb.) stand out, fruits that can be used in food, enriching, for example, bakery products. In this context, the present study aimed to study the effect of partial replacement of wheat flour by marolo pulp flour (16 %) and peel flour (external mesocarp + exocarp) of pequi (2 %) and water by marolo pulp (30 %) on the quality of sweet breads, over 5 days of storage. Two types of bread were prepared, controlled and enriched, packed in plastic bags and stored for five days in a dry and ventilated place. To compare the two formulations the following daily analyses were made: coloration, water activity, texture profile, phenolic profile, antioxidant activity, vitamin C, carotenoids and sensorial, being made centesimal analysis only at zero time. The bread enriched with fruits of the cerrado presented the highest levels of dietary fiber, carotenoids, phenolic compounds and antioxidants and was well accepted sensorially. There was an effect of storage time on daily analyses. It can be concluded, that the substitution of wheat flour for marolo pulp flour and pequi peel and of water for marolo pulp were effective in the nutritional enrichment of sweet breads, adding functional and sensorial appeal to them. The bread obtained by the new formulation can be considered a healthy alternative for school and sustainable feeding.